NUWERE ONTWIKKELINGE OP DIE GEBIED VAN DIE GESKIEDSKRYWING: 'N GELEENTHEID VIR HERBESINNING NA 350 JAAR VAN GEREFORMEERDHEID? - Lategan, Bernard C. (Scriptura, 2002)
This contribution is interested in the question: How do we remember 350 years of reformed history in South Africa? Recent developments in historiography have made it clear that the writing of history is not a reconstruction of the past, but a construct. It is in essence an act of sense-making. Against this background, two aspects of the work of church historians in the Afrikaans reformed tradition stand out: The lack of context in the presentation and the one-dimensional perspective on reformed history. The possible reasons for this type of historiography are discussed. It also raises the question what represents the true spirit of the reformed tradition. In conclusion, a call for the re-assessment of the history of the past 350 is made